The effect of strengthening health literacy in nursing homes on employee pain and consequences of pain ‒ a stepped-wedge intervention trial - Anne Konring Larsen; Lau Caspar Thygesen; Ole Steen Mortensen; Laura Punnett; Marie Birk Jørgensen (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVE: This study examined the effectiveness of a workplace health literacy intervention on pain intensity, bothersomeness of pain, and sickness absence. METHODS: The quasi-experimental stepped-wedge cluster trial evaluated an intervention with two elements: (i) courses for employees and management to organize a joint foundation of knowledge about pain prevention and management with communication tools, and (ii) structured dialogs between employee and supervisor, to develop action plans to prevent and reduce pain. Monthly measurements were taken of pain intensity (0-10 scale), bothersomeness (days/month), and pain-related absence (days/month). RESULTS: Six workplaces were recruited, and 88% of employees (509) participated in evaluations. At baseline, mean pain level was 4.0, mean bothersomeness was 3.8 days/month, and mean pain-related absence was 0.6 days/month. From linear mixed models, pain intensity was reduced by -0.28 [95% confidence interval (CI) -0.52- -0.04] corresponding to a 7% reduction. For employees with pain >3 at baseline, the reduction was -0.74 (95% CI -1.11- -0.38) or 12%. There was no significant mean change in bothersomeness or sickness absence among all employees. CONCLUSION: This intervention was both feasible and effective in shifting the overall mean pain level downwards for the entire population by 7%, with an accentuated effect among employees with pain levels >3. Organizing health literacy in nursing homes might be a feasible and effective way to build work environment efforts targeting the needs of employees. Future studies should investigate whether organizing health literacy is effective in other workplace settings and for employees with other health challenges.